THE EFFECT OF INTERCROPPING ON CROP PRODUCTIVITY AND YIELD QUALITY OF OAT (Avena sativa L.)/ GRAIN LEGUMINOUS SPECIES (PEA – Pissum sativum L., LENTIL – Lens culinaris L.) CULTIVATED IN PURE STAND AND MIXTURES, IN THE ORGANIC AGRICULTURE SYSTEM - Dusa, Elena Mirela; Stan, Vasilica (European Scientific Journal, ESJ, 2013)
Intercropping is the simultaneous cultivation of two or more species on the same field, during a growing season, in order to produce a greater yield, by making use of resources that would otherwise not be utilized by a single crop. The researches are focused on the productivity and yield quality of oat and two species of grain leguminous (pea – Pisum sativum L. and lentil – Lens culinaris L.), in intercropping, in order to evaluate their adaptability to natural conditions of South Romania and to organic cultivation. The experiment was carried out in 2007-2009 period, in Moara Domneasca Experimental Field, on reddish preluvosoil, in randomized variants, in 4 replications. The seeds used for experiments were organic. Oat and grain leguminous were sown in alternating rows (1 row of oat, 1 row of pea/lentil), at 12.5 cm between rows. A series of parameters were determined as follows: yield components, yield, land equivalent ratio and seeds quality. In average, the oat intercropped with pea produced 14.02 q/ha, and the oat intercropped with lentil had 13.47 q/ha. In intercropping, the pea yield was 7.87 q/ha smaller than in the sole cropping (27.48 q/ha). The lentil intercropped with oat produced 7.69 q/ha. The highest value of LER (1.50) was obtained at oat-pea intercropping. At oat-lentil intercropping, LER value was 1.40. The highest protein yield was obtained at pea in sole cropping, i.e. 733 kg/ha. Within intercrops, the best protein yield was obtained in oat-pea intercropping (6.96 q/ha); for comparison, the oat-lentil intercropping produced 3.67 q/ha protein.﻿